John Greenleaf Whittier and his relation to the abolition of slavery - Griffing, Augusta (My University, 1904)
Introduction: Among our American poets stands one whose fame is not derived merely from the literary quality of his work. For many years political and humanitarian interests caused his poetical abilities to become merely a means to an end. Not until the prime of life was past did he find himself free to write as a poet and not as an advocate. The best years of his manhood were given to the work of furthering a just but unpopular cause- a cause wherein he was often misunderstood and unappreciated.
Citation: Griffing, Augusta. John Greenleaf Whittier and his relation to the abolition of slavery. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: John Greenleaf Whittier; Abolitionist; Poet; American Poets; Theses; Manuscripts (documents)